2014
DOI: 10.1371/journal.pone.0094915
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prolonged Exposure to Hypobaric Hypoxia on Oxidative Stress, Inflammation and Gluco-Insular Regulation: The Not-So-Sweet Price for Good Regulation

Abstract: ObjectivesThe mechanisms by which low oxygen availability are associated with the development of insulin resistance remain obscure. We thus investigated the relationship between such gluco-insular derangements in response to sustained (hypobaric) hypoxemia, and changes in biomarkers of oxidative stress, inflammation and counter-regulatory hormone responses.MethodsAfter baseline testing in London (75 m), 24 subjects ascended from Kathmandu (1,300 m) to Everest Base Camp (EBC;5,300 m) over 13 days. Of these, 14 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
38
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 50 publications
(65 reference statements)
2
38
1
Order By: Relevance
“…We have previously described the development of increased insulin resistance with prolonged exposure to hypobaric hypoxia [20]. However, the multivariate model reported in the present study suggests a concomitant decline of FFM and insulin concentrations during the expedition.…”
Section: Discussioncontrasting
confidence: 61%
“…We have previously described the development of increased insulin resistance with prolonged exposure to hypobaric hypoxia [20]. However, the multivariate model reported in the present study suggests a concomitant decline of FFM and insulin concentrations during the expedition.…”
Section: Discussioncontrasting
confidence: 61%
“…At rest, the ascent (Møller et al, 2001;Siervo et al, 2014;Taylor et al, 2012) and descent (González et al, 2005) from altitude has been shown to cause marked increases in lipid peroxidation. The participants in the current study had not been exposed to altitude for at least 4 months, minimizing the impact of prior exposure perturbing basal or exercise-induced redox state, which has previously been demonstrated in active individuals (Sanchari et al, 2010;Sinha et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Despite lower partial oxygen pressures at altitude, an exaggerated rate of reactive oxygen and nitrogen species (RONS) production is known to be coupled with weakened enzymatic and nonenzymatic antioxidants systems, eliciting increased oxidative stress. For example, previous investigations in humans have observed elevated blood biomarkers of oxidative stress (e.g., lipid peroxidation (Siervo et al, 2014;Taylor et al, 2010)) and a decline in reduced: oxidized glutathione ratio (Joanny et al, 2001;Taylor et al, 2010) at rest, relative to measures at sea level.…”
mentioning
confidence: 98%
See 2 more Smart Citations